Exploring peer learning module vs. conventional tutorials: effects on engagement and learning outcomes among first-year medical students - Vinay Arasappa Vishwanath; Sindhu Raghuramaiah; Kavita Rasalkar (BMC Medical Education)
Abstract Background In contemporary medical education, it is essential to raise student involvement and active participation in the learning process. By contrasting small-group peer learning modules with teacher-led conventional tutorial sessions, we aim to provide insights into their respective influences on learning outcomes and the overall learning experience among 150 first-year medical students. Methods Each group consisted of 50 students. These students were further divided into two groups and a pretest was administered on the day of the session. One group engaged in conventional tutorials, while the other participated in a peer learning module. Post-tests and session feedback were provided after each session. Results Results from the posttest revealed advancement in both learning approaches compared to the pretest. Compared to tutorials, the level of progress was much higher following peer learning with a p-value of < 0.05. Participants felt that while the tutorials helped them cover the full subject and saved time, they occasionally got monotonous and there was little active engagement. Students who participated in the peer learning method said that while interaction aided in a better learning experience, improved communication skills, and had more active participation, there was less time for discussion and some group members were reticent and ineffective in explaining the concepts. Conclusions The peer learning module is thought to be superior to conventional tutorial classes since it promises active involvement from all students, promotes greater learning, and aids in skill improvement, thus assisting students to help each other in gaining insight into the process of active learning.